The Influence of Organizational Culture, Motivation, and Leadership on the Performance of Palembang High Court Employees - Asmawati, Asmawati; Rahayu, Sri; Choiriyah, choriyah (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
This study aims to determine the effect of organizational culture, motivation, and leadership on the performance of Palembang High Court employees. To determine the effect of organizational culture on the performance. To determine the effect of motivation on the performance and the influence of leadership on the performance. This type of research is associative. The sample in this study was 155 respondents with a technique in collecting samples using the cluster random sampling technique. The data used in this study are primary, namely the number of respondents, agency profiles, and secondary data collection methods, namely the questionnaire. The analysis technique used is multiple linear regression analysis. The study results show that: (1) There is a positive and significant influence of organizational culture, motivation, and leadership on the performance of Palembang High Court employees. (2) Organizational culture has a positive and significant influence on performance. (3) Motivation has a positive and significant effect on the. (4) There is no positive and significant influence of organizational culture, motivation, and leadership on the performance of Palembang High Court employees. (2) Organizational culture has a positive and significant influence on performance. (3) Motivation has a positive and significant effect on the. (4) There is no positive and significant influence of organizational culture, motivation, and leadership on performance (2) There is a positive and significant influence of organizational culture on the performance of Palembang High Court employees. (3) Motivation has a positive and significant effect on performance (4) There is no positive and significant influence of organizational culture, motivation, and leadership on the performance of Palembang High Court employees.